From Herland to Gilead: Framing Post-Feminine Fertility in Dystopian and Utopian Fiction - Joseph Padios Casibual (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
There is something structurally amiss in a culture that only values women for their capacity to bear a child which is reflected in misrepresentations in literature that confined women to stereotypes that creates an endless room for debate as to what future is in store for women particularly in post-humanist literature. This paper addresses how female fertility is framed in the texts of Margaret Atwood- The Handmaid’s Tale and The Testaments (dystopian) and Charlotte Perkins Gilman- Herland and With Her in Ourland (utopian). Using transitivity analysis, it aims to examine representation and roles attached to feminine fertility, to discourse fertility in utopian and dystopian texts, and evaluate the politics of the female body in relation to fertility and reproduction. Clearly, Atwood’s dystopian fiction critically examined the oppressive and utilitarian view towards the female body which contrasted with Gilman’s utopic body autonomy. It is revealed that a sense of feminine liberty is associated with utopian fiction contrary to body bondage depicted in dystopian texts which have deeply elaborated a politicized view towards the future of the post-female body and women in general.